Cognitive, Neuropsychiatric, and Motor Features Associated With Apolipoprotein E ∊4 Allele in a Sample of Bulgarian Patients With Late-Onset Parkinson's Disease. (November 2014) - Pavlova, Radka; Mehrabian, Shima; Petrova, Maria; Skelina, Silvia; Mihova, Kalina; Jordanova, Albena; Mitev, Vanio; Traykov, Latchezar
Objective: To evaluate the role of apolipoprotein E ( APOE ) ∊4 allele on cognitive, neuropsychiatric, and motor features in a sample of Bulgarian patients with late-onset Parkinson's disease (LOPD, age at onset > 55 years). Methods: A total of 16 patients with LOPD having APOE ∊3/∊4 genotype were compared to 30 patients with LOPD having APOE ∊3/∊3 genotype and 20 healthy control individuals. Detailed cognitive assessment and evaluation of neuropsychiatric and motor symptoms were performed. Results: The patients with LOPD had significantly lower scores in all cognitive domains compared to controls. The patients with LOPD carrying an ∊4 allele showed some significant differences in their cognitive, motor, and neuropsychiatric features. Conclusions: The data suggest a role of the APOE genotype as a disease-modifying factor.